PENDIDIKAN MUHAMMADIYAH YANG BERKEMAJUAN BERBASIS KESANTUNAN BERBAHASA (Studi Perkembangan Amaliah Syariah Islam di Desa Karang Puluhan) - Ngalim, Abdul (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2015)
This paper aims to describe the development of Islamic Shari'a charity in Karang Puluhan, Jatinom District, Klaten regency. Especially with regard to improvement of Muhammadiyah education, both informal and formal Muhammadiyah. Descriptive qualitative method. Data Obtained by experience seeing facts (empiric), observations, and the phenomenon of life in society Generally, and in particular Muhammadiyah members. Technique analysis, interpretation and interaction. There are three things as a result of research. (1) The process of improvement stems from Muhammadiyah education looked Efforts to change the system and improving the quality of life of human resources is still limited level of education, low economic situation, as well as Islamic law combines running with superstition, heresy , and  superstition (TBC) Became feasible level of education, and the economy, as well as running the Islamic Shari'a, without confounding with tuberculosis. (2) The process of education to produce graduates who are godly, Lotty character, intelligent, skilled and responsible, Among the which requires effective communication concepts (Appropriate) and efficient (maximum effort and prayer, the result is optimal). (3) The effective communication, Including the selection of politeness language, and can be studied in Islamic socio-pragmatics.